2016
DOI: 10.1007/s00381-016-3258-0
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and vitamin D status in children with epilepsy, cerebral palsy, and cerebral palsy with epilepsy

Abstract: Abnormal BMD is a common problem in patients with CP and CP + E. Abnormal BMD was related to the severity of CP, but not to vitamin D levels or AED treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 25 publications
3
15
1
1
Order By: Relevance
“…The same study indicated that the duration of treatment and the number of AEDs subscribed (monotherapy or polytherapy) were correlated with abnormal BMD to a greater extent. Moreover, other studies have indicated that polytherapy treatment for epilepsy in children is related to decreased BMD levels [8][9][10]. In parallel, a study by Yaghini et al indicated that both cytochrome p450 inducing and non-inducing AEDs had caused a reduction of BMD although epileptic children without treatment had no decrease in BMD.…”
Section: Aeds and Vitamin Dsupporting
confidence: 51%
See 4 more Smart Citations
“…The same study indicated that the duration of treatment and the number of AEDs subscribed (monotherapy or polytherapy) were correlated with abnormal BMD to a greater extent. Moreover, other studies have indicated that polytherapy treatment for epilepsy in children is related to decreased BMD levels [8][9][10]. In parallel, a study by Yaghini et al indicated that both cytochrome p450 inducing and non-inducing AEDs had caused a reduction of BMD although epileptic children without treatment had no decrease in BMD.…”
Section: Aeds and Vitamin Dsupporting
confidence: 51%
“…Authors suggested that the direct influence of anticonvulsants to osteoblasts and osteoclasts may be one of the major mechanisms which lead to ERBD [7]. However, other studies have proposed that epilepsy is associated with increased bone turnover [4,8,10,11,17,20]. Although the major indication for this association is the elevated ALP levels, this can be also attributed to increased bone absorption as ALP is not a specific biomarker for bone turnover [6].…”
Section: Aeds and Bone Cells And Bone Turnovermentioning
confidence: 95%
See 3 more Smart Citations